Literacy Analysis of Information and Communication Technology for Vocational High School Teachers in Using Augmented Reality Media - Fatma Sukmawati; Nashniq Shah Bin Majiri (Universitas Sebelas Maret, 2022)
Information and communication technology (ICT) literacy is a fundamental skill that every educator must possess in the 21st century. This study looks at the category of ICT literacy levels of accounting teachers in vocational high schools. This research is quantitative descriptive. The research sample consisted of 35 accounting teachers at a vocational high school in Surakarta. Five categories were used to categorize the level of ICT literacy, while the aspects measured in ICT literacy comprised six domains: access, manage, integrate, evaluate, create, and communicate. Data were collected using the methods of observation, interviews, and questionnaires. Data obtained through questionnaires were then analyzed using descriptive analysis techniques with percentages. The results showed that the six aspects measured in each category, on average, were in the relatively good category, the level was quite good (40%), the level was good (22%), and the level was very good (20%). It explains that ICT literacy in utilizing augmented reality media combines the ability to access, intellectually, interpret, communicate, and new skills to effectively use information and communication technology.